Efficient Propane-Ethane Fractionation within Petrochemical Plant Operations - Nnadikwe Johnson; Onuoha Fidelis Wopara (Journal Majelis Paspama, 2026)
Efficient propane-ethane fractionation is crucial in petrochemical complexes, enabling the production of high-purity products. This paper focuses on the treatment of ethane-propane mixtures recovered from natural gas, highlighting the interplay between key units: Gas Sweetening Unit (GSU), C2/C3 Recovery Unit, and Gas Cracker Unit (GCU). In the GSU, acid gases like CO2 are removed via chemical absorption using solvents like DEA, preventing freezing issues in downstream cryogenic processes. The 'sweetened' gas feeds into the C2/C3 Recovery Unit, where cryogenic conditions enable efficient ethane-propane separation. Optimizing fractionation in this unit enhances GCU performance, boosting ethylene and propylene yields. Process integration and energy efficiency are critical considerations. This study explores efficient propane-ethane fractionation strategies, aiming to improve overall petrochemical complex performance. Key aspects of this process include effective CO2 removal in the GSU, ensuring process reliability. Cryogenic separation in the C2/C3 Recovery Unit enables high-purity product recovery. The impact on GCU performance is significant, as efficient fractionation boosts downstream yields. Energy-efficient fractionation strategies are also crucial for reducing operating costs and environmental impact. By optimizing these aspects, petrochemical complexes can improve product yields, reduce energy consumption, and enhance overall efficiency. This research contributes to the development of efficient propane-ethane fractionation technologies, supporting the growth of the petrochemical industry.